Identification of soluble solid content and total acid content using real-time visual inspection system - Moorthy, C. H. V. K. N. S. N.; Tripathi, Mukesh Kumar; Hudagi, Manjunath R.; Hadimani, Lingaraj A.; Chavan, Gayatri Sanjay; Angadi, Sanjeevkumar (Indonesian Journal of Electrical Engineering and Computer Science, 2024)
This paper presents the framework for identifying materials using a fused descriptor-based approach, leverage computer vision techniques. The system is structured into three phases: derivation, extraction, and portrayal. Initially, the system employs K-means gathering techniques for establishing derivation. Following derivation, the system utilizes variety, texture, and shape-based feature extraction methods to extract relevant features from the soluble solid content and total acid content using real-time visual inspection system. A “consolidating” fusion feature is explored in the final phase using classification algorithms like C4.5, support vector machines (SVM), and k-nearest neighbors (KNN). The performance evaluation of the recognition system demonstrates promising results, with accuracy rates of 97.89%, 94.60%, and 90.25% achieved by using C4.5, SVM, and KNN separately. This indicates that the proposed fusion strategy effectively supports accurately recognizing materials using a fused descriptor-based approach.